Colour in calibration points indexing - Nowakowski, Artur; Skarbek, Władysław (Photonics Letters of Poland, 2009)
The paper presents the way that colour can serve solving the problem of calibration points indexing in a camera geometrical calibration process. We propose a technique in which indexes of calibration points in a black-and-white chessboard are represented as sets of colour regions in the neighbourhood of calibration points. We provide some general rules for designing a colour calibration chessboard and provide a method of calibration image analysis. We show that this approach leads to obtaining better results than in the case of widely used methods employing information about already indexed points to compute indexes. We also report constraints concerning the technique. Full Text: PDF References: A. Nowakowski, W.Skarbek, Proc. KKRRiT, Poznań, 149 (2006). A.Nowakowski, M.Tomaszewski, Proc. Networked Audiovisual Media Technologies KKRRiT, 2005, Kraków, 7 (2005) A. Nowakowski, W. Skarbek, Opto-Electronics Review, 15, 4, 202 (2007). T. H. Cormen, C. E. Leiserson, R. L. Rivest, Introduction to algorithms, McGraw-Hill (1981). A. Nowakowski, W. Skarbek, Proc. of SPIE 6159, 1051 (2006).